Geospatial variability of soil and climate on performance of rubber (Hevea brasiliensis Muell. Arg.) in traditional region of India - Meti, S.; Meerabai, M.; Jacob, J.; Saifudeen, M. (Journal of Plantation Crops, 2014)
Natural rubber is grown in traditional region of India in varied soil and climate conditions. Earlier efforts to relate soil-site condition on performance of rubber were based on observation of few locations. Geospatial analysis of soil and climate variation helps to delineate constraint areas for site specific management. Kanyakumari district of Tamil Nadu and Kasaragod district of Kerala having contrasting soil and climate condition in traditional region of rubber cultivation were selected to study the effect of soil and climate on rubber performance. Soil OC, available P and K in Kanyakumari was in medium range whereas in Kasaragod soil OC was in high range, available P and K in low range. In Kanyakumari district major rubber growing area was under low elevation (0-100 m) and slope below 5-10 per cent compared to low to medium(100-200 m) elevation and slope above 5-10 per cent in Kasaragod. Annual rainfall distributed uniformly in Kanyakumari compared to unimodal rainfall distribution observed in Kasaragod. As a result Moisture Adequacy Index (MAI) in Kanyakumari during December to March was good to poor whereas in Kasaragod it was poor to very poor. Length of growing period was more in Kanyakumari compared to Kasaragod as a result performance of rubber with respect to growth and yield was better in Kanyakumari than Kasaragod. Factor analysis showed that soil health (OC) and cation (Ca and Mg) factors showed significant role in performance of rubber in Kanyakumari, whereas in Kasaragod only topographic factors i.e., elevation showed significant role in rubber performance.